2018
DOI: 10.3390/geosciences8060224
|View full text |Cite
|
Sign up to set email alerts
|

Room for Rivers: Risk Reduction by Enhancing the Flood Conveyance Capacity of The Netherlands’ Large Rivers

Abstract: Abstract:The Netherlands has just finished implementing the Room for the Rivers program along the Rhine and Meuse Rivers in response to increasing river discharges. Recently, making more room for the river is, however, being challenged for future application because the flood defenses are assessed to be too weak and will need reinforcement anyway. To be able to decide on the most desirable policy for the remainder of the century, we require knowledge of all benefits and costs of individual interventions and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 22 publications
0
45
0
Order By: Relevance
“…Finally, we want to emphasise that our current definition of robustness for rivers deviates from that of Mens (2015) in the sense that it pertains to the river alone instead of to the entire flood risk system and it is limited to the river's function of discharging water. Elsewhere (Asselman & Klijn, 2016;Klijn et al, 2018), we showed that higher river flood levels in the Rhine and Meuse Rivers translate into an increase in consequence of flooding. To our opinion, this provides a valid argumentation to at least prevent that climate change results in higher flood levels and hence to enhance the conveyance capacity of our rivers.…”
Section: Meuse Rivermentioning
confidence: 82%
“…Finally, we want to emphasise that our current definition of robustness for rivers deviates from that of Mens (2015) in the sense that it pertains to the river alone instead of to the entire flood risk system and it is limited to the river's function of discharging water. Elsewhere (Asselman & Klijn, 2016;Klijn et al, 2018), we showed that higher river flood levels in the Rhine and Meuse Rivers translate into an increase in consequence of flooding. To our opinion, this provides a valid argumentation to at least prevent that climate change results in higher flood levels and hence to enhance the conveyance capacity of our rivers.…”
Section: Meuse Rivermentioning
confidence: 82%
“…(3) decrease of the impacts by landslides and slope instability at the coastal sediment amount level [68]; (4) decrease of the risk of injuries among the park visitors due to slope instability of interesting hiking paths during heavy rainfalls; (5) support for the interaction between private landowners; (6) integration of the proposed NBS with regional policies for land management/planning and with the Basin Master Plan [69,70]; (7) improvement of the visibility and governance model of the Portofino Natural Regional Park, also in the perspective of becoming a National Park; and (8) improvement of the collaboration between the park authority and the stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…(6) The reduced hydraulic capacity of the rivers makes them insufficient to transport the flows safely. (7) Several areas are highly vulnerable. For example, the villages of San Fruttuoso and Paraggi, which have already suffered repeated damage from geo-hydrological events in the last century.…”
Section: Selected Locations and Hazards For The Reconect Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…"Room for rivers" (Klijn et al, 2018) represents another form of "building with nature" suggesting to widen the embankments and create side channels, so there would be more room for rivers to enable to managing higher water levels during floods. However, in flood protection systems, to reach an optimum resilience there should be a trade-off between this approach (increasing the absorbing and adaptive capacity of the system), and robust solutions such as raising dikes.…”
Section: B) Nature-based Solutions -Combined Green and Grey Infrastrumentioning
confidence: 99%